Circular Versus Linear Versus Hand-Sewn Gastrojejunostomy in Roux-en-Y-Gastric Bypass Influence on Weight Loss and Amelioration of Comorbidities: Data Analysis from a Quality Assurance Study of the Surgical Treatment of Obesity in Germany - Stroh, Christine Elisabeth; Nesterov, Grigorij; Weiner, Rudolf; Benedix, Frank; Knoll, Christian; Pross, Matthias; Manger, Thomas; , Obesity Surgery Working Group; , Competence Network Obesity (Frontiers in Surgery, 2014)
Background: Since January 1 2005, the outcomes of bariatric surgeries have been recorded in Germany. All data are registered prospectively in cooperation with the Institute of Quality Assurance in Surgery at Otto-von-Guericke University Magdeburg. Methods: Data are collected in an online data bank. Data collection began in 2005 for the results of Roux-en-Y Gastric Bypass (RYGB). In addition to primary bariatric operations, data regarding the complications and the amelioration of comorbidities have been analyzed. Participation in the quality assurance study is required for all certified centers in Germany. Results: Roux-en-Y Gastric Bypass is the most popular bariatric operation in Germany. There were 5115 operations performed from 2005 to 2010. A circular anastomosis was performed in 1587 patients, and a linear anastomosis was performed in 2734 patients. In 783 patients the hand-sewn technique was used. The leakage rate for the linear technique is 1.6%, and the leakage rate is 1.2% for circular anastomosis and 1.4% for hand-sewn technique. Conclusion: RYGB is a popular procedure in Germany. The complication rate has decreased since 2005. The amelioration of comorbidities is not influenced by the anastomosis technique. Additional data are necessary to evaluate the long-term effect of linear versus hand-sewn and versus circular stapled gastrojejunal anastomosis regarding pouch dilatation, small bowel dilatation and consecutive weight loss.